STUDENTS’ PERCEPTIONS ON THEIR ENGAGEMENT IN SMALL GROUP DISCUSSION - Vega Alviani; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The aims of this study were to describe how the students perceive their engagement in small group discussions and to explain the factors that influence the students engagement in small group discussions. A descriptive qualitative design was used in this study. The source of data was 25 students of Grade VIII SMP Al-Wasliyah 8 Medan. The data were analyzed by using descriptive qualitative. The results showed that (1) The students perceive their engagement in small group discussion positively. Most of the students agreed that being engaged in small group discussion was useful for them as EFL students and agreed that they have followed all activities in small group discussion and given their best effort. The students agreed that they could participate well in small group discussion, and felt motivated to engage themselves. The students felt that they were confident enough to deliver their opinions in group discussion. Besides, all of the students satisfied with their engagement in small group discussion. (2) The factors that influence the students in engaging in small group discussion were the students’ relationship with teachers, relationship with peers and classmates, students’ self-efficacy, students’ self-regulated learning, and students’ interest in learning.